2014
DOI: 10.1159/000358528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motive-Oriented Therapeutic Relationship in a Ten-Session General Psychiatric Treatment of Borderline Personality Disorder: A Randomized Controlled Trial

Abstract: Background: Motive-oriented therapeutic relationship (MOTR) was postulated to be a particularly helpful therapeutic ingredient in the early treatment phase of patients with personality disorders, in particular with borderline personality disorder (BPD). The present randomized controlled study using an add-on design is the first study to test this assumption in a 10-session general psychiatric treatment with patients presenting with BPD on symptom reduction and therapeutic alliance. Methods: A total of 85 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
96
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 41 publications
6
96
0
3
Order By: Relevance
“…There are 2 hypotheses for this unexpected result: (1) the MOTR therapists might have assessed the already difficult collaboration in a more mindful and 'realistic' fashion, as a correlate of the individualized PA understanding of the case, and might actually have rated the alliance overly negatively, inversely proportional to the actual subsequent patient change; (2) alternatively, as a correlate of the PA case formulation and MOTR heuristics, the therapists may have overestimated the positive relationship. The moderate-to-low therapist mean ratings of the alliance [5] would speak in favor of the first hypothesis. The MOTR may have a specific impact on the therapist's awareness and interaction style, which produces in the patient an additional symptom relief.…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…There are 2 hypotheses for this unexpected result: (1) the MOTR therapists might have assessed the already difficult collaboration in a more mindful and 'realistic' fashion, as a correlate of the individualized PA understanding of the case, and might actually have rated the alliance overly negatively, inversely proportional to the actual subsequent patient change; (2) alternatively, as a correlate of the PA case formulation and MOTR heuristics, the therapists may have overestimated the positive relationship. The moderate-to-low therapist mean ratings of the alliance [5] would speak in favor of the first hypothesis. The MOTR may have a specific impact on the therapist's awareness and interaction style, which produces in the patient an additional symptom relief.…”
mentioning
confidence: 94%
“…Among several ways of operationalizing appropriate therapist responsiveness, in the present letter we will focus on one specific method of conceptualization, i.e. Plan analysis (PA), and the motive-oriented therapeutic relationship (MOTR) [3,4] .In patients with BPD, a randomized controlled trial [5] showed that the MOTR as an operationalization of how therapists can explicitly be responsive -based on the individualized case formulation related to the PA -had an effect on the global outcome and progression of the therapeutic alliance, rated by the therapist, over the course of 10 sessions of therapy. However, it is unclear what the exact patient change processes are in treatments based on appropriate responsiveness.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for the effectiveness of MOTHER can be provided by a pilot study conducted by Kramer et al (2011), in which a reduction of interpersonal problems and a stronger therapeutic alliance was found in the early-phase treatment of patients with borderline personality disorder. In a recent study by Kramer et al (2014), these findings could be replicated and extended in a larger ten-session randomized controlled trial (RCT). The present study also has a number of limitations that might have influenced some of the results.…”
Section: Discussionmentioning
confidence: 86%